1997
DOI: 10.1007/bf02375628
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum chromite as an anode material for solid oxide fuel cells

Abstract: Abstract. The electrochemical behavior of pure lanthanum chromite and strontium dopedlanthanum chromite was studied by impedance spectroscopy under HJH20, CO/CO2 and CHJH20.Results show that the electrochemical oxidation of H2 is faster than that of CO or CH 4. Strontium doping enhances the anodic activity of the material.The impedance diagrams are composed of two semi-circles. The high frequency one does not appear to be related to a chemical or electrochemical reaction. The low frequency one is linked to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 7 publications
3
6
0
4
Order By: Relevance
“…Vernoux et al [9] have demonstrated that Lao.8Sro. 2-Cr0.9503 has interesting electrochemical properties for hydrogen oxidation, and that the ruthenium cation is a good catalyst for methane reforming [10].…”
Section: B)mentioning
confidence: 98%
“…Vernoux et al [9] have demonstrated that Lao.8Sro. 2-Cr0.9503 has interesting electrochemical properties for hydrogen oxidation, and that the ruthenium cation is a good catalyst for methane reforming [10].…”
Section: B)mentioning
confidence: 98%
“…Ainda na geração de energia, pode ser utilizado como ânodo para células de óxido sólido de temperatura intermediária (ITSOFC) [78][79][80][81][82][83].…”
Section: Aplicaçõesunclassified
“…Nas SOFCs, quando utilizado como ânodo, o LaCrO 3 , atende aos requisitos de estabilidade nas condições de operação, uma boa capacidade catalítica para os combustíveis, em particular o metano, maior tolerância à contaminação superficial por carbono, quando comparado com o cermet Ni-YSZ (niquel-zircônia estabilizada com ítria) que é o ânodo normalmente estudado [81,82,85].…”
Section: Aplicaçõesunclassified
“…Sendo por isso, adequado para aplicações como interconector em células a combustível de óxido sólido (solid oxide fuel cell -SOFC) [1][2][3][4][5], geradores magnetos hidrodinâmicos (magnetohydrodynamic generator -MHD) [6][7][8], catalisadores para queima de combustíveis [9][10][11] sensores de NO X em alta temperatura [12] e, resistências para fornos [13,14]. Ainda na geração de energia pode ser utilizado como ânodo para células de óxido sólido de temperatura intermediária (intermediate temperature solid oxide fuel cell -ITSOFC) [15][16][17][18][19][20][21]. Nas SOFCs o interconector é utilizado para promover a conexão elétrica entre o ânodo de uma célula unitária e o cátodo da célula adjacente e, atuar como uma barreira física para os gases envolvidos, evitando desta forma, a mistura do combustível (hidrogênio) do ânodo, com o ar (oxigênio) do cátodo, devendo, portanto, ser denso.…”
Section: Introductionunclassified